A case study documenting the various methods used by the local barangay unit of Matina Crossing in the post-crisis phase of the Davao City flash flood - Estacio, Remle Anne M.
Pre-crisis phase of crisis management and crisis communication is the least studied phase of Coombs? 3-phase model. Moreover, Barangay Matina Crossing bore the worst effect of the June 28, 2011 flash flood considered as the worst disaster to hit the city in decades. The aftermath of the Davao City flash flood served as a challenge for the local barangay to effectively respond and develop strategies to improve the crisis management and communication process. The prevalence of flash flood incidents in the city and the nature of natural disasters gave importance to this study. The researcher documented the various post-crisis methods employed by the barangay as presented in the interview with Barangay Secretary Mr. Leonardo Villafuerte, Barangay Kagawad Joseph Encabo, and Disaster Operations team Chief Mr. Renante Luna. The methods documented were classified into short-term and long-term methods. These post-crisis methods were analyzed by looking into what have been done in the pre-crisis and crisis phase of the Davao City flash flood. To analyze the post-crisis methods, the researcher employed the concepts of Combs? 3-Phase Model, Diffusion of Innovation Theory, and Tisch Center Scholars? Crisis Management Cycle. This study revealed the organizational learning of the barangay from the flash flood. Also, the importance of the stakeholders was strengthened by the results of the research.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication